Effect of Brand Image and Product Quality on Purchase Decisions in Using Online Travel Ticket Accommodation Provider Applications - Utami, Rahayu Tri; Ermanuri, Ermanuri; Rosita A, Shofa (Bina Bangsa International Journal of Business and Management, 2023)
The condition of business competition for online travel ticket accommodation application providers is very tight. The competition will continue because several new brands, such as Traveloka, Tiket.com, Agoda, Pegi-pegi, and others, continue to emerge. In determining the purchase decision, many consumers consider several things. Many factors influence a person's buying behavior towards a product. Each individual has different desires and tastes. Brand image (brand image) and product quality is one of the factors that influence purchasing decisions. This study uses descriptive quantitative research methods. This study's source of data using primary data, data collection by distributing questionnaires given to lecturers at the Polytechnic LP3I Jakarta. Sampling of this study used 108 respondents. The method of analysis in this study used a question instrument test using validity tests, reliability tests, multiple linear regression analysis. Hypothesis test using t test, f test, and coefficient of determination ( R2), with data processing using SPSS 25.0 program. This study aims to determine the influence of brand image (brand image) on purchasing decisions in using online ticket accommodation provider applications and the effect of product quality on purchasing decisions in using online ticket accommodation provider applications. In addition, this study also aims to determine whether brand image and product quality influence purchasing decisions